2008
DOI: 10.1038/mp.2008.106
|View full text |Cite
|
Sign up to set email alerts
|

Glial pathology in an animal model of depression: reversal of stress-induced cellular, metabolic and behavioral deficits by the glutamate-modulating drug riluzole

Abstract: Growing evidence indicates that glia pathology and amino-acid neurotransmitter system abnormalities contribute to the pathophysiology and possibly the pathogenesis of major depressive disorder. This study investigates changes in glial function occurring in the rat prefrontal cortex (PFC) after chronic unpredictable stress (CUS), a rodent model of depression. Furthermore, we analyzed the effects of riluzole, a Food and Drug Administration-approved drug for the treatment of amyotrophic laterosclerosis, known to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
346
1
5

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 405 publications
(382 citation statements)
references
References 50 publications
30
346
1
5
Order By: Relevance
“…We suggest that the downregulation of VGAT and its coupled GABA synthesising enzyme GAD65 in response to CMS could explain the decreased GABA levels observed in the frontal cortex and in the hippocampus of the CMS mice. In addition, a recent study addressing the effects of CMS on glial metabolism, has shown decreased glial GABA formation (49) which is consistent with our results. The upregulation of hippocampal EAAT1 may occur as a neuroprotective response to stressinduced elevations in glutamate in the synaptic cleft (32,33) as well as in response to increased corticosterone levels (50).…”
Section: Regulation Of Glutamate/gaba Cycle and Behaviour By Cms In Wsupporting
confidence: 82%
See 1 more Smart Citation
“…We suggest that the downregulation of VGAT and its coupled GABA synthesising enzyme GAD65 in response to CMS could explain the decreased GABA levels observed in the frontal cortex and in the hippocampus of the CMS mice. In addition, a recent study addressing the effects of CMS on glial metabolism, has shown decreased glial GABA formation (49) which is consistent with our results. The upregulation of hippocampal EAAT1 may occur as a neuroprotective response to stressinduced elevations in glutamate in the synaptic cleft (32,33) as well as in response to increased corticosterone levels (50).…”
Section: Regulation Of Glutamate/gaba Cycle and Behaviour By Cms In Wsupporting
confidence: 82%
“…Moreover, mice lacking an isoform of GAD65 have shown reduced GABA levels and increased anxiety (46,47) while rats exposed to CMS show reduced GABA levels, anhedonia and helplessness (48,49). We suggest that the downregulation of VGAT and its coupled GABA synthesising enzyme GAD65 in response to CMS could explain the decreased GABA levels observed in the frontal cortex and in the hippocampus of the CMS mice.…”
Section: Regulation Of Glutamate/gaba Cycle and Behaviour By Cms In Wmentioning
confidence: 84%
“…On the glutamatergic side, inhibition of the glutamine synthetase by MSO is known to result in a pronounced reduction of cerebral glutamate (Fonnum and Paulsen, 1990;Ghoddoussi et al, 2010). Likewise, riluzole is supposed to reduce neural glutamate levels by its polypharmacological action as suppressor of presynaptic vesicular glutamate release and enhancer of EAAT-mediated glutamate scavenging that together convey anticonvulsant and neuroprotective therapy (Banasr et al, 2010;Kim et al, 2007). Hence, our pharmacoMRS assessments have indeed faithfully reported these anticipated primary pharmacological effects of the latter prototypical GABAergic and glutamatergic interventions.…”
Section: Neuropharmacological Relevancementioning
confidence: 81%
“…Animals expressing learned helplessness showed a significantly suppressed expression of the glial glutamate transporter GLT1 (rodent nomenclature for EAAT2) in hippocampus and cerebral cortex compared with non-helpless animals and littermates with low levels of helplessness (Zink et al, 2010). Reduced glial fibrillary acidic protein (GFAP) expression is observed following chronic unpredictable stress (CUS) is associated with depressive-like behaviors in rodent models, and pharmacological treatments that attenuate the effects of CUS on of GFAP expression and/or facilitate EAAT function can reverse the cellular and behavioral effects of CUS (Banasr et al, 2010;Czeh et al, 2006;Gourley et al, 2012;Mineur et al, 2007;Sanacora and Banasr, 2013) Induction of anhedonia in laboratory animals by inhibition of astroglial surface (plasmalemmal) glutamate transporters (Bechtholt-Gompf et al, 2010;Ongur et al, 2014). Reduced coupling between gap junctions of astroglial cells in prefrontal cortex associated with reduced expression of connexin-43 (gap junction) proteins leading to anhedonia following pharmacological inhibition of gap junctional conductance or chronic stress in laboratory animals (Sun et al, 2012).…”
Section: Box 1 Examples Of Evidence Suggesting a Role For Astrocyte Pmentioning
confidence: 99%